Confronting Gentrification: Can Creative Interventions Help People Keep More than Just Their Homes? (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2019)
Gentrification is changing the landscape of many American cities. As land values rise, people may lose their homes, neighbors, and sites of significance, along with their sense of place, community, and history. There is a critical need to build and preserve affordable housing, yet housing alone will not address the more than material losses. What role can the arts play in sustaining place attachments, restoring relationships, and building place knowledge in gentrifying neighborhoods? This paper explores this question through a systematic review of current research. We identify four prominent alternative interventions in gentrifying neighborhoods—creative placemaking, public pedagogy, community organizing, and public science—and explicate strengths and limitations of each approach. We find the strongest interventions bridge approaches—engaging artists as/and researchers, educators, and community leaders—and mobilize residents as participants in knowledge/cultural production. We note that initiatives that provide short-term benefit may simultaneously make the neighborhood more desirable—and thus more vulnerable to gentrification—in the longer-term. Finally, given the dearth of research in this area, we conclude with recommendations for future research that attends to issues of equity, process as well as outcome, and longitudinal effects of more than material interventions in gentrifying neighborhoods.